2016
DOI: 10.1128/aem.01802-16
|View full text |Cite
|
Sign up to set email alerts
|

The Bacterial Mobile Resistome Transfer Network Connecting the Animal and Human Microbiomes

Abstract: Horizontally acquired antibiotic resistance genes (ARGs) in bacteria are highly mobile and have been ranked as principal risk resistance determinants. However, the transfer network of the mobile resistome and the forces driving mobile ARG transfer are largely unknown. Here, we present the whole profile of the mobile resistome in 23,425 bacterial genomes and explore the effects of phylogeny and ecology on the recent transfer (>99% nucleotide identity) of mobile ARGs. We found that mobile ARGs are mainly present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
202
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 280 publications
(216 citation statements)
references
References 45 publications
9
202
2
3
Order By: Relevance
“…In another study, antibiotic perturbation of the microbiota caused blooms of multidrug-resistant E. coli in the intestine, which subsequently caused bacteremia and sepsis (Ayres, Trinidad and Vance 2012). In addition, the genomic structure of Proteobacteria contains the highest number of MGEs (Hu et al 2016). Another study reported that E. coli was the most highly represented carrier of antibiotic resistance in all tested groups (Osterblad et al 2000).…”
Section: Higher Abundance Of Args In Tcdd-dosed Micementioning
confidence: 97%
“…In another study, antibiotic perturbation of the microbiota caused blooms of multidrug-resistant E. coli in the intestine, which subsequently caused bacteremia and sepsis (Ayres, Trinidad and Vance 2012). In addition, the genomic structure of Proteobacteria contains the highest number of MGEs (Hu et al 2016). Another study reported that E. coli was the most highly represented carrier of antibiotic resistance in all tested groups (Osterblad et al 2000).…”
Section: Higher Abundance Of Args In Tcdd-dosed Micementioning
confidence: 97%
“…To our knowledge, this plasmid and its variants have not been found in S. Typhimurium. The antibiotic resistance genes are frequently exchanged among E. coli, K. pneumoniae, and S. enterica serovars (27), and the conjugation experiments in this study showed that the plasmid carrying mcr-1.6 can transfer from S. Typhimurium to E. coli and K. pneumoniae. Therefore, the presence of mcr-1.6 in clinical E. coli and K. pneumoniae strains needs to be a focus in public health surveillance.…”
mentioning
confidence: 99%
“…Selective reduction of ARGs using anaerobic digestion also correlated with reduced counts of the intI1 gene (Burch et al, 2016). Determined via whole genome sequence analysis of 23,425 bacterial genomes (Hu et al, 2016), the sulfonamide resistance gene sul1 , which is typically associated with intI1 (Luo et al, 2010), was observed with the greatest number of different ARGs types. As such, the high correlation between the intI1 gene LAMP assay and abundance of ARGs indicates its utility for monitoring ARGs in river samples.…”
Section: Discussionmentioning
confidence: 99%